Preparation and rheological study of pentaerythritol triacrylate grafted onto polypropylene induced by air plasma. Issue 42 (6th June 2019) - Meng, Xiao‐Mei; Ma, Zhe; Ma, Gui‐Qiu; Sheng, Jing
ABSTRACT: The surface modification of isotactic polypropylene by dielectric barrier discharge of air plasma is studied. The air plasma induces melt grafting of pentaerythritol triacrylate onto polypropylene, which successfully introduces polar long‐chain branching (LCB) structure into polymer bulk. The results of X‐ray photoelectron spectroscopy show that C─O and CO oxygen‐containing functional groups are formed on polypropylene surface, of which the functional groups contents can reach 24.4 and 12.0%, respectively. It is found that there is an optimum plasma treatment time of 4 min to obtain the high peroxides concentration of about 3.38–3.69 × 10 −7 mol cm −2 . The highest grafting degree of this plasma method is 1.79%, which achieves the same level as the chemical grafting method. The molecular structural change of the graft‐modified polypropylene, in the form of LCB is investigated by shear rheology. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48054. Abstract : Storage modulus versus angle frequency for PiPP and iPP‐g‐PETA.